Optimization of mother’s understanding of the “isi piringku” complementary feeding program through audiovisual media as an effort to prevent stunting - Dian Rahmi; Rikayoni Rikayoni (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting remains a major maternal and child health concern globally, with long-term consequences on physical growth, cognitive development, and future productivity. In 2020, an estimated 149 million children under five years of age were affected by stunting worldwide. In Indonesia, the prevalence of stunting reached 24.4% in 2021, indicating a persistent public health challenge. Inadequate maternal knowledge and inappropriate complementary feeding practices, particularly related to animal-source protein intake, contribute significantly to stunting during the critical first 1,000 days of life. Innovative nutrition education strategies are therefore needed to improve maternal knowledge and attitudes toward optimal infant and young child feeding. Purpose: to evaluate the effectiveness of audiovisual media in improving mothers’ knowledge and attitudes regarding “Isi Piringku” complementary feeding practices, with a focus on animal-source protein intake, as an effort to prevent stunting. Method: A pre-experimental study with a one-group pretest–posttest design was conducted among mothers of children aged 6–24 months in the working area of Ikur Koto Primary Health Center, Padang, Indonesia. Participants were selected using incidental sampling. Nutrition education was delivered using audiovisual media. Data were analyzed using the Shapiro–Wilk test for normality and a one-sample t-test with a significance level of p < 0.05. Results: The results demonstrated a statistically significant improvement in mothers’ knowledge and attitudes after the audiovisual-based nutrition education intervention. Mothers showed better understanding of balanced complementary feeding practices, particularly the importance of animal-source protein in preventing stunting. Conclusion: Audiovisual-based nutrition education is an effective strategy to enhance maternal knowledge and attitudes regarding complementary feeding practices. This approach has strong potential to support stunting prevention programs within maternal and child health services.